Comparison of the treatment efficacy of herpes zoster neuralgia with temporary spinal cord stimulation at different sites - Xin Hu; Xiaolong Ye; Liu Wang; Yilun Wu; Zenghua Zhou; Shengrong Xu; Ruilin He; Zongbin Jiang (Frontiers in Neurology)
BackgroundZoster-associated pain (ZAP) is a common complication after herpes zoster infection. In recent years, conventional temporary dorsal column stimulation (tDCS) has been widely used nationally and internationally as a safe and effective minimally invasive treatment for ZAP. It has also been shown that temporary dorsal nerve root stimulation (tDNRS) may also be an effective treatment for ZAP. However, there is no direct clinical comparison between the newer tDNRS and the conventional tDCS.ObjectiveTo compare the procedure time, radiation dose, efficacy and cost of the tDNRS and tDCS for the treatment of ZAP. And the complications of the two surgical modalities were recorded.MethodsEighty patients with ZAP who attended the pain department of the Second Affiliated Hospital of Guangxi Medical University from January 2022 to July 2023 were selected. They were divided into tDNRS group (n = 40) and tDCS group (n = 40) by using random number table method. The operation time, radiation dose, number of electrodes used, cost of medical consumables, and number of postoperative electrical stimulation adjustments were recorded for each case, and the patients’ pain level, sleep quality, quality of life, and overall efficacy were analysed and compared at preoperative (T0), 1 week (T1), 1 month (T2), 2 months (T3) and 3 months (T4) after the operation.ResultsA total of 76 patients were finally enrolled, 38 in the tDNRS group and 38 in the tDCS group. During the 3-month follow-up period, all patients showed a significant decrease in Numerical Rating Scale (NRS) and Pittsburgh Sleep Quality Index (PQSI) scores and a significant increase in quality of life (QL-Index scale) scores after treatment with both methods. And there was no statistically significant difference between the two methods. However, patients who received tDNRS had a significantly shorter operative time and less intraoperative radiation exposure than those who received tDCS (p < 0.0001), and the mean number of postoperative stimulation parameter adjustments and the cost of medical consumables were significantly lower than those in the tDCS group (p < 0.0001).ConclusionBoth tDNRS and tDCS were effective in the treatment of ZAP, but tDNRS had the advantages of more precise coverage, shorter procedure time, less radiation exposure, fewer electrical stimulation adjustments, and lower cost.